Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) terhadap Hasil Belajar Fisika - Harmila; Kamaluddin; I Wayan Darmadi (Universitas Tadulako, 2021)
This study aimed to know the effect of the Two Stay Two Stray (TSTS) type cooperative learning model on physics learning outcomes. This type of research was a quasi-experimental design with a non-randomized pretest-posttest control group. The population of this study were all students of class X SMA Negeri 5 Palu. The sampling technique used in this study was purposive sampling with the research sample being class X MIPA 3 as the experimental group and class X MIPA 4 as the control group. The instrument used is a test of learning outcomes in the form of multiple-choice questions. The increase in the average N-Gain in the experimental class was 50.88% while in the control class it was 22.68%. Based on the hypothesis test t-test (one party) obtained tcount = 2.88 and t0.975 (67) = 2.00 at the real level = 0.05. This means that the value of tcount is outside the acceptance area of ​​H0. So it can be concluded that there is an effect of student learning outcomes using the Two Stay Two Stray (TSTS) type cooperative learning model on physics learning outcomes in class X SMA Negeri 5 Palu